My war : a love story in letters and drawings - Sugarman, Tracy, 1921-2013. (New York : Random House, 2000)
Presents watercolor paintings, sketches, drawings, and photographs, combined with narrative that describes life on the front lines, his feelings about being separated from his wife, and the events of the Allied invasion of Europe.
Keywords: Sugarman, Tracy, -- 1921-2013 -- Correspondence; World War, 1939-1945 -- Personal narratives, American; Soldiers -- United States -- Biography; World War, 1939-1945 -- Campaigns -- Western Front